PELATIHAN MENJAHIT TINGKAT DASAR - Rajamemang; Andi Tenri Ulmi Kalsum; Andi Muh Rusdi Maidin; Wahyudi Putera; Nisma Iriani; Wahyuti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Basic sewing skills training is a form of community empowerment aimed at improving human resource capacity and economic independence. This community service program was conducted in Tallo District, Makassar City, targeting housewives and young women who had not previously acquired sewing skills. The implementation method consisted of preparation, execution, and evaluation stages through lectures, demonstrations, and hands-on practice. The training materials included the introduction of sewing tools and materials, basic sewing techniques, and the production of simple sewing products. The results showed a significant improvement in participants’ knowledge and practical sewing skills, as evidenced by their ability to operate sewing equipment and independently create simple products. Furthermore, the program increased participants’ motivation to develop home-based businesses, thereby contributing to improved family welfare and sustainable economic empowerment.